PEMBERDAYAAN KELOMPOK IBU PKK DESA BORISALLO DALAM USAHA PEMBUATAN SABUN HOTEL BERBAHAN HERBAL BUNGA KERSEN - St. Maryam; Rahmawati; Rusli (Akademi Farmasi Yamasi Makassar, 2024)
Borisallo Village is one of the villages in Parangloe District, Gowa Regency, which consists of two hamlets, namely: Pakkolompo and Bontojai. The target of activities in Borisallo village is the group of PKK women whose main livelihood is as housewives or working in the agricultural field/garden sector. Currently, the various needs of society are increasing, so that along with this, economically, people's income must also increase. This community service activity aims to provide business ideas by utilizing herbal plants found in the community to make hotel soap products that can be sold both directly and online. The formula for the soap provided uses the natural active ingredient of cherry blossoms so that in this community service, education will be provided on how to use traditional plants as a basic ingredient for active substances (antiseptics) which can be processed into a hygiene product, namely solid soap, and participants will make their own soap in accordance with given formula. From the results of this activity, participants gained an increased understanding of the use of traditional medicine and knew how to produce hotel soap and then package the soap in attractive and labeled plastic packaging. Apart from that, the level of participants' understanding can be assessed from the results of the pre and post tests carried out, where their understanding increases by implementing good and clean processing, packaging and labeling methods. What can be concluded is that the participants have the skills to make solid soap after receiving training and can sell it to increase economic value to the community. It is hoped that this product will obtain a patent and halal certificate.